The Effect of Velocity-Based Training on Inducing Postactivation Performance Enhancement - Fan, Ziqi; Fan, Zilin; Zhao, Zhiwei; Zou, Yu; Zhang, Qingwen (International Journal of Sports Medicine, 2025)
This systematic review and meta-analysis aimed to evaluate the effect of velocity-based training (VBT) conditioning activities (CA) on subsequent athletic performance and explore how different CA types, velocity loss (VL) thresholds, loads, sets, participants, and rest intervals influence postactivation performance enhancement (PAPE). Six electronic databases were searched. Nine studies were included, reporting 18 effect sizes and comprising 152 participants. We assessed pre- and posttest differences using meta-analysis, conducted subgroup analyses to identify potential moderating factors, and employed nonlinear meta-regression to explore the relationship between rest intervals and the PAPE effect. The results showed that VBT-CA significantly improved athletic performance. Subgroup analyses showed no significant differences; nevertheless, bench press-type CA, CA with VL≤10%, load≥80% one-repetition maximum (1RM), single-set CA, and athlete population exhibited a trend toward larger PAPE effects. Between 5.77 and 12.8 minutes after VBT-CA, a significant PAPE effect was indicated by the meta-regression results, with the optimal time point being 8.96 minutes. Our study suggests that VBT-CA can effectively induce the PAPE effect. Individuals seeking to improve their athletic performance could consider performing a single set of CA with load≥80% 1RM, VL≤10%, 5.8–12.8 minutes before the explosive activity.
Keywords: velocity loss threshold; resistance training; rest interval; conditioning activity